Cross-cultural adaptation and validation of the cancer survivors’ unmet needs measure among gynecological cancer patients in Indonesia - Haryani, Haryani; Afiyanti, Yati; Besral, Besral; Gayatri, Dewi; Wahidi, Kemala Rita; Pramiasti, Hana; Milanti, Ariesta (Archive of Oncology, 2019)
Background: The number of gynecological cancer survivors in Indonesia is growing, yet little is recognized about their supportive care needs due to a lack of validated assessment to measure them. This study aimed to culturally adapt the Cancer survivors’ unmet needs into Indonesian language and to test its validity and reliability for Indonesian gynecological cancer patients. Methods: We performed the translation and adaptation of the Cancer survivors’ unmet needs based on Beaton’s cross-cultural adaptation process of self-report measure. We then evaluated the psychometric properties of Cancer survivors’ unmet needs -Indonesian with 298 participants from three hospitals across Indonesia. Results: Five factors were extracted from Exploratory Factor Analysis with factor loading >0.4. Cancer survivors’ unmet needs -Indonesian had negative correlations with The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 , indicating that the higher score of unmet needs resulted in the lower score of quality of life. The Cronbach’s a coefficient for the Cancer survivors’ unmet needs-Indonesian ranged from 0.75-0.95. Conclusions: The Cancer survivors’ unmet needs-Indonesian version offers a valid and reliable scale for assessing supportive care needs among Indonesian gynecological cancer patients. The Cancer survivors’ unmet needs-Indonesian could help clinicians to assess supportive care needs among Indonesian gynecological cancer patients. The low-resource countries such as Indonesia could use the evidence from the Cancer survivors’ unmet needs assessment to develop the supportive care service in the clinical settings.